Dimensional stabilization od tropical harwoods with polyethylene glycol - Chudnoff, M.; Goytia, E. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
The effect of PEG-1000 (polyethylene glycol) in controlling wood shrinkage was determined using 11 tropical wood species. Treatments were cold soaking for 2, 4, or 6 weeks followed by blast drying of the green wood (Program 1) or by a combination of air drying and blast drying (Program 11).